1989
DOI: 10.2307/3430544
|View full text |Cite
|
Sign up to set email alerts
|

Potential Bronchoconstrictor Stimuli in Acid Fog

Abstract: Acid fog is complex and contains multiple stimuli that may be capable of inducing bronchoconstriction. These stimuli include sulfuric and nitric acids, the principal inorganic acids present; sulfites, formed in the atmosphere as a reaction product of sulfur dioxide and water droplets; fog water itself, a hypoosmolar aerosol; the organic acid hydroxymethanesulfonate, -the bisulfite adduct of formaldehyde; and gaseous pollutants, e.g., sulfur dioxide, oxides of nitrogen, ozone. Given this complexity, evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
1989
1989

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In a series of papers from the Cardiovascular Research Institute, Balmes et al (13) and Fine et al (14) have examined the hypothesis that H+ availability is the primary stimulus for the increase in airway resistance observed with acid aerosol inhalation in asthmatics. At this symposium, Balmes summarized evidence that supports the titratable acidity hypothesis previously described (14).…”
Section: Response Mechanismsmentioning
confidence: 99%
“…In a series of papers from the Cardiovascular Research Institute, Balmes et al (13) and Fine et al (14) have examined the hypothesis that H+ availability is the primary stimulus for the increase in airway resistance observed with acid aerosol inhalation in asthmatics. At this symposium, Balmes summarized evidence that supports the titratable acidity hypothesis previously described (14).…”
Section: Response Mechanismsmentioning
confidence: 99%
“…Insofar as acid fogs are hypoosmotic (10), this mechanism may operate for a wide range of acid aerosols. He showed that at low (and high) pH, mucus, and especially the glycoproteins in mucus, lose their buffering capacity, and the mucus increases in ViSCositly.…”
Section: Basic Mechanisms Of Effectsmentioning
confidence: 99%